1995
DOI: 10.1002/pen.760350505
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of material properties during physical aging

Abstract: Aging experiments using the NIST (National Institute of Standards and Technology) torsional dilatometer have been performed in which the temperature of an isothermally equilibrated epoxy glass was abruptly changed to a new temperature To and the evolution of the volume and torsional relaxation responses recorded. The results of down-jump and up-jump experiments were found to differ dramatically. Not only is the normal asymmetry of volume approach to equilibrium found, but the mechanical responses are found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 23 publications
1
78
0
1
Order By: Relevance
“…The reason for this is our feeling that the effects of structure on the structural (volume, enthalpy) recovery response need not be the same as for the viscoelastic (creep, relaxation) response. Thus, although the changing thermodynamic state obviously impacts the kinetics of both structural recovery and creep or stress relaxation, its impact need not be the same for the different processes [14][15][16][17][18][19][20].…”
Section: Physical Aging In Polymer Glassesmentioning
confidence: 99%
“…The reason for this is our feeling that the effects of structure on the structural (volume, enthalpy) recovery response need not be the same as for the viscoelastic (creep, relaxation) response. Thus, although the changing thermodynamic state obviously impacts the kinetics of both structural recovery and creep or stress relaxation, its impact need not be the same for the different processes [14][15][16][17][18][19][20].…”
Section: Physical Aging In Polymer Glassesmentioning
confidence: 99%
“…For samples equilibrated at a series of high temperatures and then subjected to a temperature jump to a common lower temperature, the approach to equilibrium is qualitatively different than if the samples each began at equilibrium at a lower temperature and then are subjected to a T jump to a common higher temperature. 8 It should be noted that molecular dynamics simulations cannot access the time scales of minutes, hours, days, and weeks relevant to many practical applications, but it is possible to perform temperature jump experiments in the supercooled regime to observe significant aging of thermodynamic and relaxation properties. This is the approach of the present paper and other recent studies of the aging effect in glass-forming materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, dilatometry has been widely used to monitor the changes in volume of polymers at different temperatures in the glassy state. [6][7][8] Recently, fluorescence method using probe molecules with the internal rotations sensitive to viscosity was also utilized to examine the aging phenomena of polymers.9 Furthermore, an X-ray diffraction method was recently proposed for monitoring the strain distribution in amorphous materials, 10 which would be able to provide a potential tool for studies on physical aging.Recently, we have developed a Mach-Zehnder interferometer (MZI) equipped with a high-pressure Mercury lamp (350 W, Moritex, Japan) to in situ monitor the time-evolution process of the strain in photoreactive polymers.11 In this study, the nanometer deformation was in situ observed for a poly(ethyl acrylate) cross-linked with 365 nm UV light of different intensities. The aging phenomena and the corresponding kinetics were observed and analyzed via the dependence of the deformation on irradiation time and cross-link density.…”
mentioning
confidence: 99%